2016
DOI: 10.1080/09637486.2016.1221385
|View full text |Cite
|
Sign up to set email alerts
|

Food quality, effects on health and sustainability today: a model case report

Abstract: The Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico is a five-century institution that, besides the unique clinical role in the center of Milan, may rely on benefactor donations such as fields and farming houses not far from the city, for a total of 8500 ha, all managed by the "Sviluppo Ca' Granda' Foundation". Presently, the main products of these fields are represented by rice and cow's milk. During the latest years, farmers and managers have developed a model of sustainable food production, with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[9] Moreover, a recent systematic review confirmed Boers's findings reporting GI values for rice ranging between 19 and 116. [10] The most of studies conducted in order to evaluate the GI of rice were conducted on Indica rice, [2,9] while few studies have been carried out on the japonica varieties [11,12] ; specifically a study was conducted on the Carnaroli cultivar; the GI value of the Carnaroli rice cultivar evaluated in this study is 64%. [11] Furthermore, few studies have been conducted to evaluate the relationship between amylose content and GI in Japonica rice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[9] Moreover, a recent systematic review confirmed Boers's findings reporting GI values for rice ranging between 19 and 116. [10] The most of studies conducted in order to evaluate the GI of rice were conducted on Indica rice, [2,9] while few studies have been carried out on the japonica varieties [11,12] ; specifically a study was conducted on the Carnaroli cultivar; the GI value of the Carnaroli rice cultivar evaluated in this study is 64%. [11] Furthermore, few studies have been conducted to evaluate the relationship between amylose content and GI in Japonica rice.…”
Section: Introductionmentioning
confidence: 97%
“…The most of studies conducted in order to evaluate the GI of rice were conducted on Indica rice, [ 2,9 ] while few studies have been carried out on the japonica varieties [ 11,12 ] ; specifically a study was conducted on the Carnaroli cultivar; the GI value of the Carnaroli rice cultivar evaluated in this study is 64%. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%